CLINICAL CHARACTERISTICS AND MANAGEMENT OF EMERGENCY CONDITIONS IN PEDIATRIC DENTISTRY - Islamova Nilufar Bustanovna; Tursunov Diyorbek (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Angioedema Schwinke’s edema is an immediate allergic reaction, manifested by angioedema spreading to the skin, subcutaneous tissue, and mucous membranes. Clinical diagnosis It is characterized by the sudden appearance of limited edema in places with loose subcutaneous tissue, thickets of the lips, auricles, neck, hands, feet. Edema can often reach significant sizes and deform the affected area. The immediate danger of this reaction is the frequent development of mechanical asphyxia due to edema of the upper respiratory tract. With laryngeal edema, the child has a barking cough, hoarseness of voice, difficulty inhaling and, possibly, exhaling due to the bronchospasm joining. If the tongue swells, speech becomes difficult, and the processes of chewing and swallowing are disrupted.